Digital Social Multitasking (DSMT), Friendship Quality, and Basic Psychological Needs Satisfaction Among Adolescents: Perceptions as Mediators. - Yang, Chia-chen; Pham, Thomas; Ariati, Jati; Smith, Christina; Foster, Misti D. (Journal of Youth & Adolescence, 2021)
Most existing research assumes "phone use during face-to-face interactions" to be psychosocially detrimental. Drawing on the digital social multitasking framework, this study explored not only the negative but also positive implications of the behavior. A sample of 517 adolescents (M = 14.83, S.D. = 1.93; 50% female) recruited through the Qualtrics panel completed an online survey. Results showed that adolescents' and their friend's digital social multitasking were both associated with (1) greater perceived efficiency, which, in turn, was associated with competence need satisfaction, and (2) greater perceived connection, which, in turn, was associated with better friendship quality, autonomy need satisfaction, and relatedness need satisfaction. Adolescents' own multitasking also had an indirect, negative relationship with friendship quality through perceived distraction, but friend's multitasking did not compromise friendship quality. The study provides a more balanced picture, showing that despite the potential harm of digital social multitasking, adolescents' phone use during face-to-face peer interactions also involves potential benefits for teens' psychosocial well-being.